The Effects Of Constructivist-Strategies And Direct Instruction Using Multimedia On Achievement Among Learners With Different Psychological Profiles - Kong, Sow Lai (2006)
The main research question of the study was "Do two different instructional strategies contribute to differences in learning at different levels of knowledge tasks for learners with different psychological profiles on the Chemistry topic of the Periodic Table ?" Two modes of instruction, Constructivist-Strategies Instruction (CSI) and Direct Instruction (DI), using similar validated multimedia materials were taught by teacher assistants following protocols and supervised by two assessors, for a period of 5 weeks. Six research questions associated with six hypotheses (together with the subhypotheses) were formulated and tested using inferential statistics (l-tests). All hypotheses formulated were a priori directional hypotheses and tested at the level of significance of p< 0.05. Other existing variables were analysed using Correlation, ANCOVA, and Stepwise Linear Regression to determine the contributions towards the dependent variables. The study used a 2X2 quasi-experimental factorial design with repeated measures for the moderator variables in a non-equivalent Control Group Pretest- Postlest Design, involving a total of 156 Form Four students aged between 16 to 17 years old from four rural secondary schools. Intact classes were randomly assigned the CSI or DI mode of instruction, the independent variable of this study. The dependent variables were the mean gain score for lower and higher order knowledge tasks and the problem solving score. Moderator variables were the Cattell measure for intelligence/ability and the internal locus of control (LOC) of students.